On estimates of minima of criterion functions in optimization on combinations - Emets, O. A.; Roskladka, О. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
On the basis of the approach proposed, we obtain new estimates of extremal values of strongly convex differentiable functions and strengthened estimates of minima on a set of combinations with repetions.